Educação corporativa no estado de Goiás: o programa Universidade Corporativa e a formação dos servidores públicos - COSTA, Larissa Neves (2007)
This work complete the line of research of State and Educational Politics, of the Program of After-Graduation in Education of the Federal University of Goiás. It analyzes the formation of the state public servers, on the basis of the Program Corporative University of the State of Goiás (Prounico), initiate in 2004. The Prounico searchs to institute a new standard of formation of public officers, basing itself on a conception of education of pragmatic and instrumental character. A historical research and with emphasis to a particular case was become fullfilled theoretician-documentary: the Prounico. From an ample revision of literature, analysis and critical interpretation of the data, the research indicated that the principles norteadores of the actions of qualification offered by the State of Goiás the public servers, for intermediary of the Prounico, do not contemplate a ampler and critical formation, come back for the construction of a full citizenship. The qualification proposal for the servers contemplates the development of abilities and the competitive strategy of training, in tune with the education perspective as merchandise used for the increase of a supposed competitiveness of the State of Goiás in global scope. The present logic is not of the public sphere, the common good, the democracy, of the intervention and offers, gratuitous and with quality, of health, education, culture and scientific research, amongst others. One is about a managemental logic, based for a economic rationality guided by the rules of the private initiative